IoT-based automatic water circulation to control the pH level of water in hydroponic plants - Abdullah Munawwar; Ferdy Riza (Lembaga Riset Mutiara Akbar, 2026)
Water pH stability is a crucial factor in hydroponic systems because it directly affects the ability of plants to absorb nutrients. A common problem is that the process of monitoring and controlling pH is still done manually, making it less efficient and potentially causing imbalances in the plant's environmental conditions. This study aims to design and implement an Internet of Things (IoT)-based automatic water circulation system to control water pH levels in hydroponic plants. The research method is carried out through system design using an ESP32 microcontroller integrated with pH sensors, temperature sensors, and light sensors, as well as actuators in the form of a water pump and UV lamp. This system is capable of monitoring conditions in real time and performing automatic control connected to a website-based platform. The results of the study show that the system is able to maintain pH stability in the optimal range of 6.5–7.5 with a good level of accuracy and increases efficiency in hydroponic management. Thus, this system can be an effective and practical solution in supporting technology-based hydroponic plant cultivation.